PENERAPAN MODEL PEMBELAJARAN KOOEPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SEKOLAH DASAR - Samsur Samsur (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This research is motivated by the lack of IPS student learning outcomes can be seen from the results of thestudents' social studies class V SD Negeri 54 Sebangar with an average value of 60.65. Therefore, theresearchers provide an alternative implementation strategies in the classroom to the application of learningmodels kooeperatif make a match type in the class V SD Negeri 54 Sebangar in the academic year 2014/2015.This research aims to improve learning outcomes IPS V grade students of SD Negeri 54 Sebangar with theapplication of learning models kooeperatif make a match type in the class V Implementation Strategy. Form ofresearch is the Classroom Action Research (PTK) with 2 cycles. Based on research data anlisis after applying oflearning models kooeperatif make a match type, the average percentage of the activity of teachers in the firstcycle 74.99% increased to 91.06% in the second cycle. The average percentage of student activity alsoincreased, namely 67.85% in the first cycle increased to 82.14% in the second cycle. Student learning outcomesin basic score by the average value of 60.65 and the first cycle increased with an average value of 75.00 classwith a 23.66% increase in the percentage of learning outcomes and the percentage of students who completed84.61%, and the second cycle increased again by an average of 82.30 with the percentage improvement classlearning outcomes 35.69% and the percentage of students who completed 88.46%. These results indicate that theapplication the application of learning models kooeperatif make a match type in the class V IPS grade studentsof SD Negeri 54 Sebangar.